Surface seawater pCO2 observations in the Atlantic Ocean measured with a membrane-based sensor and collected for an instrument intercomparison experiment - Vlad Alexandru Macovei; Oliver Listing; Nadja Kinski; Yoana G Voynova (PANGAEA, 2025)
An instrument intercomparison experiment was performed on the San Lorenzo Maersk (formerly Cap San Lorenzo) container ship. Here we show the results from the HydroC CO2-FT membrane-based pCO2 instrument, which was installed next to the existing installation of a General Oceanics (GO) showerhead equilibrator system. The functioning principle of the HydroC involves dissolved CO2 molecules passing the flow head and diffusing through a TOUGH membrane into an internal gas circuit. The mole fraction of CO2 is determined using a temperature stabilized non-dispersive infrared spectrometer (NDIR). The partial pressure of carbon dioxide was calculated in the surface water pumped to the engine room from the ship extquotesingles underway system. The data were quality-controlled, processed according to the manufacturer instructions, and interpolated on a 1-minute time grid. The experiment took place between 2021 and 2023 over two phases and nine journeys (each up to 11 days long). During phase one (2021), a standard version of the HydroC was used. During phase two (2023), a prototype version with integrated cleaning cycle was used. The last journey in phase two (October-November 2023) also benefited from gas standard correction. The data were collected in the Atlantic Ocean, on transects between the coasts of Europe (Algeciras, Spain) and South America (Santos, Brazil). The pCO2 data in this data submission come from the membrane-based sensor; the pCO2 data from the GO instrument are available on the SOCAT database.